Aplikasi Manual Book Alat Berat Berbasis Android - Muhammad Raehan; Untung Suwardoyo; Sudirman Sahidin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
The advancement of information technology offers wide opportunities in the development of interactive learning media, one of which is through Android-based devices. In the field of construction, understanding heavy equipment is crucial for students and civil engineering learners. Unfortunately, the lack of engaging and accessible learning media limits the understanding of the types and functions of heavy construction equipment. This study aims to develop an Android-based application for the introduction of heavy construction equipment as an interactive learning medium. The method used in this study is Research and Development (R&D), which includes several key stages such as: identifying problems and potentials, data collection, product design, validation, revision, testing, and final product refinement. The application includes various types of heavy equipment such as excavators, bulldozers, cranes, dump trucks, and motor graders, equipped with images, function descriptions, and interactive features. Validation was conducted by subject matter experts and media experts, while user trials were carried out among selected participants. The evaluation results show that the application is feasible to be used as a learning medium, with high scores in terms of content quality, user interface, and ease of use. This application is expected to support self-directed learning about heavy construction equipment in a more engaging and accessible way, especially for users in educational and technical training environments